The breakaway ebook A novel. - Weiner, Jennifer (2023)
From #1 New York Times bestselling author Jennifer Weiner comes a warmhearted and empowering new novel about love, family, friendship, secrets, and a life-changing journey. Thirty-three-year-old Abby Stern has made it to a happy place. True, she still has gig jobs instead of a career, and the apartment where she's lived since college still looks like she's just moved in. But she's got good friends, her bike, and her bicycling club in Philadelphia. She's at peace with her plus-size body—at least, most of the time—and she's on track to marry Mark Medoff, her childhood sweetheart, a man she met at the weight-loss camp that her perpetually dieting mother forced her to attend. Fifteen years after her final summer at Camp Golden Hills, when Abby reconnects with a half-his-size Mark, it feels like the happy ending she's always wanted. Yet Abby can't escape the feeling that something isn't right...or the memories of one thrilling night she spent with a man named Sebastian two years previously. When Abby gets a last-minute invitation to lead a cycling trip from NYC to Niagara Falls, she's happy to have time away from Mark, a chance to reflect and make up her mind. But things get complicated fast. First, Abby spots a familiar face in the group—Sebastian, the one-night stand she thought she'd never see again. Sebastian is a serial dater who lives a hundred miles away. In spite of their undeniable chemistry, Abby is determined to keep her distance. Then there's a surprise last-minute addition to the trip: her mother, Eileen, the woman Abby blames for a lifetime of body shaming and insecurities she's still trying to undo. Over two weeks and more than seven hundred miles, strangers become friends, hidden truths come to light, a teenage girl with a secret unites the riders in unexpected ways...and Abby is forced to reconsider everything she believes about herself, her mother, and the nature of love.